2011
DOI: 10.1177/0734282910395894
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Psychometric Properties of the Test Anxiety Scale for Elementary Students (TAS-E) Scores

Abstract: The psychometric properties of the Test Anxiety Scale for Elementary Students (TAS-E) scores were examined. In Study 1, an exploratory factor analysis (EFA) was performed on the responses of 997 students in Grades 2 to 6 on the TAS-E. The results of the EFA produced a four-factor solution: Physiological Hyperarousal, Social Concerns, Task Irrelevant Behavior, and Worry. Gender differences were also found on each factor, except the Social Concerns factor. In Study 2, a confirmatory factor analysis (CFA) was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 30 publications
3
45
0
4
Order By: Relevance
“…Las importantes consecuencias negativas para el desarrollo de los niños justifican su estudio (Freudenthaler et al, 2008;Isolan et al, 2011;Kaplan et al, otras investigaciones en este ámbito, las cuales explicaban la presencia de dichas diferencias por tres hipótesis diferenciadas: Hipótesis Biológica, Hipótesis Sociocultural e Hipótesis Psicológica (Brumariu & Kerns, 2010;Freudenthaler et al, 2008;Fujita et al, 2009;García-Fernández et al, 2010;Isolan et al, 2011;Lowe et al, 2011;Orgilés et al, 2008). Según la hipótesis biológica, las diferencias se deberían a las propias características genéticas distintivas de hombres y mujeres.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Las importantes consecuencias negativas para el desarrollo de los niños justifican su estudio (Freudenthaler et al, 2008;Isolan et al, 2011;Kaplan et al, otras investigaciones en este ámbito, las cuales explicaban la presencia de dichas diferencias por tres hipótesis diferenciadas: Hipótesis Biológica, Hipótesis Sociocultural e Hipótesis Psicológica (Brumariu & Kerns, 2010;Freudenthaler et al, 2008;Fujita et al, 2009;García-Fernández et al, 2010;Isolan et al, 2011;Lowe et al, 2011;Orgilés et al, 2008). Según la hipótesis biológica, las diferencias se deberían a las propias características genéticas distintivas de hombres y mujeres.…”
Section: Discussionunclassified
“…Centrándonos en las diferencias existentes en la manifestación de este trastorno, numerosos estudios demuestran que las chicas, independientemente del grupo de edad al que pertenezcan, manifiestan mayores niveles de ansiedad escolar que los chicos (Brumariu & Kerns, 2010;Freudenthaler et al, 2008;Fujita et al, 2009;García-Fernández, Espada, Orgilés, & Méndez, 2010;García-Fernández, Inglés, Lagos-San Martín, Gonzálvez, Vicent, & Gómez-Núñez, 2016;Isolan et al, 2011;Leikanger, Ingul, & Larsson, 2012;Lowe, Grumbein, & Raad, 2011;Orgilés, Espada, Méndez, & García-Fernández, 2008). Los autores barajan tres posibles hipó-tesis que explicarían dichas diferencias: La primera de ellas es la hipótesis biológica, que establece que las mujeres y los hombres son diferentes debido a sus propias características genéticas.…”
unclassified
“…Findings relating to the development of test anxiety components are, however, less clear-cut than those focusing simply on overall test anxiety. Lowe, Grumbein, and Raad (2011) found that students in lower grades endorse similar levels of cognitive interference and worry, resulting in nonsignificant differences. Similarly, Wren and Benson (2004) indicated that students' test anxiety regarding the thoughts, off-task behaviors, and autonomic reactions components tends to be stable as they progress through primary to middle school.…”
Section: Gender and School-level Differencesmentioning
confidence: 98%
“…Los resultados obtenidos en este estudio apoyan los obtenidos en investigaciones anteriores, en los cuales se señala que las mujeres (niñas y adolescentes) puntúan más alto en ansiedad que los hombres (niños y adolescentes) (Boyd, Ginsburg, Lambert, Cooley y Campbell, 2003;Burnham, 2005;Burnham y Gullone, 1997;Essau, Muris y Ederer, 2002;Freudenthaler, Spinath y Neubauer, 2008;García-Fernández et al 2010;Hale, Raaijmakers, Muris y Meeus, 2008;Leikanger et al 2012;Lowe et al 2011;March, Sullivan y Parker, 1999;Masi, Sbrana, Poli, Tomaiuolo, Favilla y Marcheschi, 2000;Méndez, García-Fernández y Olivares, 1996;Muris, 2002;Puskar, Sereika y Haller, 2004;Steinhausen, Müller y Winkler, 2008;Tejero, 2006;Valiente et al 2003;Wren y Benson, 2004). Situación que en este estudio se reitera en todos los indicadores evaluados (situaciones y respuestas), encontrándose diferencias estadísticamente significativas en todos ellos y tamaños del efecto de pequeña a moderada magnitud.…”
Section: Conclusionesunclassified